Development of Online Needs-Based Workshop Support System in a Pandemic - Murata, Hidenori; Horio, Seisuke; Kobayashi, Hideki (Frontiers in Sustainability, 2021)
The sustainable development goals, adopted in 2015, include achievement of sustainable consumption and production (SCP) patterns as the 12th goal. To achieve SCP patterns, it is necessary not only to reduce environmental load caused by production and manufacturing but also to improve the sufficiency of fundamental human needs and the quality of life of consumers. The living-sphere approach aims to design products for a target living-sphere by determining the sufficiency of fundamental human needs among local residents through products using the fundamental human needs framework proposed by Max-Neef. This framework consists of fundamental human needs and satisfiers. Max-Neef argued that fundamental human needs are universal, but satisfiers fulfilling these fundamental human needs depend on region, culture, and time. The satisfiers have previously been extracted by needs-based participatory workshops, but during the ongoing coronavirus disease 2019 (COVID-19) pandemic, these face-to-face workshops can no longer be held. In this study, we developed an online needs-based workshop support system. The developed system consists of digital applications such as an online whiteboard service, video meeting service and original software to support facilitation. We applied our system to online needs-based workshops in Japan and compared the results of these online workshops and those of the face-to-face workshops held until last year to analyze and validate the online needs-based workshop support system.